1999
DOI: 10.2190/un7p-9rxy-j9h5-bhn6
|View full text |Cite
|
Sign up to set email alerts
|

Children's Grief Narratives in Popular Films

Abstract: Children's grief narratives, conceptualized as portrayals of the grief process in children, in popular films are examined. Four films focus this study: Snow White, Bambi, The Land Before Time, and The Lion King. These films reflect a range of acknowledgment of death and descriptions of grief in their young characters. They also vary in the extent to which they are consistent with traditional models of grief that emphasize detachment and contemporary models that focus on the importance of ongoing connections wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…In contrast with Sedney (1999Sedney ( , 2002 who found positive aspects of portrayals of death in children's films, Schultz and Huet (2001) examined the highest grossing American films and Academy Award nominees and concluded that the majority of portrayals of death are unrealistic and sensational, and are rarely accompanied by realistic and normal grief reactions. This was true about some children's films as well.…”
Section: Popular Children's Films Children's Grieving Processes Andmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast with Sedney (1999Sedney ( , 2002 who found positive aspects of portrayals of death in children's films, Schultz and Huet (2001) examined the highest grossing American films and Academy Award nominees and concluded that the majority of portrayals of death are unrealistic and sensational, and are rarely accompanied by realistic and normal grief reactions. This was true about some children's films as well.…”
Section: Popular Children's Films Children's Grieving Processes Andmentioning
confidence: 92%
“…In general, there is limited research that examines the relationship between popular children's films and children's comprehension of death. For instance, Sedney (1999) examined the portrayal of grief in young characters in children's films. The films all had hopeful messages showing the possibility for a happy life following the death of a loved one.…”
Section: Popular Children's Films Children's Grieving Processes Andmentioning
confidence: 99%
“…In times past, one function of literature, particularly fairy tales and oral stories, was to help children to understand and develop a sense of meaning about the world they lived in [49]. While this role continues today, researchers acknowledge that for modern children, conveyors of these messages are more likely to be movies and television shows [6]. It is estimated that children under 8 years of age spend an average of 3 h per day consuming media, with the majority of that time dedicated to film and television [50,51].…”
Section: Media Portrayals Of Death and Dyingmentioning
confidence: 99%
“…Alongside concerns about unrealistic and inaccurate depictions of death and grief in the mainstream media, there is also recognition that carefully crafted media portrayals can have a positive influence on children's understanding of death [6,52,58,59]. For example, there is a small children's literature on death education, aimed at providing facts about death and suggesting ways to cope and normalize grief [59].…”
Section: Media Portrayals Of Death and Dyingmentioning
confidence: 99%
See 1 more Smart Citation